Effects of Adult Literacy Programme on Acquisition of Cake Baking Vocational Skills among Prison Inmates in Plateau State, Nigeria - Aliu, Charity Ukwo (NIU Journal of Social Sciences, 2019)
This study investigated the Effects of Adult Literacy Programme on Acquisition of Cake Baking Vocational Skills among Prison Inmates in Plateau State, Nigeria. Based on the aim and objectives of the study, two research questions and two hypotheses were postulated to guide the study. The study adopted the non-equivalent pre-test, post-test experimental group research design, whereby participants were assigned to experimental and control groups. The population of the study was made up of 1474 inmates from two selected prisons in Plateau State, comprising Jos and Lamingo.  A sample of 40 convicted prison inmates were randomly selected for the study. They represent 20 experimental and 20 control groups. The instrument for data collection was Prison Inmate Skill Acquisition Preference Indicator (PISAPI) with content validity index of 0.80 and a reliability index of 0.78.  Descriptive statistic of mean and standard deviation was used to answer the research questions and inferential statistics of t-test was used to test the hypotheses at 0.05 level of significance. Results revealed that prison inmate in the experimental group performed better in cake baking and event decoration than inmate in the control group. The researcher recommend that teachers should use more of Adult literacy program in the prison on cake making and event decoration should be encouraged which will help equip the inmates face the economic challenges of the society and be self-employed. Keywords: Prison inmate, Adult literacy program  cake baking, vocational skills and prison inmates